2001
DOI: 10.1149/1.1357172
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Hydrous Ruthenium Oxide-Carbon Supercapacitors

Abstract: It is shown that composite Ru oxide-carbon based supercapacitors possess superior energy and power densities as compared to bare carbon. An electroless deposition process was used to synthesize the ruthenium oxide-carbon composites. Ru is dispersed on the carbon matrix as small particles. The effect of electrochemical oxidation and temperature treatment on the material performance has been studied extensively. Increasing the oxidation temperature reduces the proton transport rate and also increases the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 14 publications
2
89
0
3
Order By: Relevance
“…2(a) and 2(b)), which can be attributed to the low ESR of the hybrid RuO 2 nanowire/printed SWNT nanostructured films. The shape of these CV curves is also different from that of the printed SWNT supercapacitors, due to the pseudocapacitance contributed by RuO 2 nanowires via electrochemical protonation [36],…”
Section: Resultsmentioning
confidence: 87%
“…2(a) and 2(b)), which can be attributed to the low ESR of the hybrid RuO 2 nanowire/printed SWNT nanostructured films. The shape of these CV curves is also different from that of the printed SWNT supercapacitors, due to the pseudocapacitance contributed by RuO 2 nanowires via electrochemical protonation [36],…”
Section: Resultsmentioning
confidence: 87%
“…The pH and bath temperature were controlled to prevent precipitation of Ru. The bath composition and deposition conditions have been reported previously [16]. The amount of carbon used for deposition was kept constant (1 g).…”
Section: Methodsmentioning
confidence: 99%
“…Sato et al [15] reported a 20% increase in speci®c capacitance by loading 7.1 wt.% Ru in activated carbon. In a previous publication, [16] we reported results from a RuO 2 ±C composite synthesized using an electroless deposition technique. It is seen that Ru is dispersed on the carbon matrix in the form of very small particles.…”
Section: Introductionmentioning
confidence: 99%
“…One strategy includes the different RuO 2 preparation methods [4,[8][9][10][11][14][15][16][17][18][19][20][21][22][23], whereas several authors recognized the importance of both intra-and inter-particle electronic conductivities and prepared the composite materials of RuO 2 with various forms of carbon [6,18,19,[27][28]. It was observed that nano-structured RuO 2 particles were decisive factor in achieving the high gravimetric capacitance [29,30].…”
Section: Introductionmentioning
confidence: 99%